Pengaruh Gaya Kepemimpinan Transformasional dan Motivasi Kerja Terhadap Kinerja Karyawan Dealer Motor Kawasaki Matahari Langgeng Jaya Tambun Bekasi - Noviana Ayu Anjar Dewi; Zahra Z; Athiy Dina Rosihana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the influence of transformational leadership style and work motivation on employee performance at Kawasaki Matahari Langgeng Jaya Motorcycle Dealer, Tambun Bekasi. Transformational leadership is a leadership approach that focuses on enhancing employee motivation, enthusiasm, and performance through inspiration, idealized influence, intellectual stimulation, and individualized consideration. Meanwhile, work motivation refers to internal and external drives that encourage employees to achieve specific goals optimally in the workplace. The research method used is quantitative with a descriptive associative approach. The population consists of all 37 employees, all of whom were selected as samples using a saturated sampling technique. Data were collected through questionnaires, observations, interviews, and documentation. Data analysis includes validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test (partial), F-test (simultaneous), and coefficient of determination (RÂ²), using SPSS version 29. The results show that partially, transformational leadership has a positive and significant effect on employee performance, with a t-count of 5.220 t-table 2.032 and a significance value of 0.008 0.05. Work motivation also has a positive and significant partial effect, with a t-count of 5.895 t-table 2.032 and a significance of 0.001 0.05. Simultaneously, both independent variables significantly influence employee performance, as shown by an F-count of 21.300 F-table 3.28 and a significance of 0.001 0.05. The coefficient of determination (RÂ²) of 0.556 indicates that 55.6% of the variation in employee performance is explained by transformational leadership and work motivation, while the remaining 44.4% is influenced by other factors outside this study.